An emergency department nurse led intervention to facilitate serious illness conversations among seriously ill older adults: A feasibility study. (May 2023) - Ouchi, Kei; Lee, Rachel S.; Block, Susan D.; Aaronson, Emily L.; Hasdianda, Mohammad A.; Wang, Wei; Rossmassler, Sarah; Palan Lopez, Ruth; Berry, Donna; Sudore, Rebecca; Schonberg, Mara A.; Tulsky, James A.
Background: Serious illness conversations may lead to care consistent with patients' goals near the end of life. The emergency department could serve as an important time and location for these conversations. Aim: To determine the feasibility of an emergency department-based, brief motivational interview to stimulate serious illness conversations among seriously ill older adults by trained nurses. Design: A pre-/post-intervention study Settings/participants: In an urban, tertiary care, academic medical center and a community hospital from January 2021 to January 2022, we prospectively enrolled adults ⩾50 years of age with serious illness and an expected prognosis <1 year. We measured feasibility outcomes using the standardized framework for feasibility studies. In addition, we also collected the validated 4-item Advance Care Planning Engagement Survey (a 5-point Likert scale) at baseline and 4-week follow-up and reviewing the electronic medical record for documentation related to newly completed serious illness conversations. Results: Among 116 eligible patients who were willing and able to participate, 76 enrolled (65% recruitment rate), and 68 completed the follow-up (91% retention rate). Mean patient age was 64.4 years (SD 8.4), 49% were female, and 58% had metastatic cancer. In all, 16 nurses conducted the intervention, and all participants completed the intervention with a median duration of 27 min. Self-reported Advance Care Planning Engagement increased from 2.78 pre to 3.31 post intervention (readiness to "talk to doctors about end-of-life wishes, " p  < 0.008). Documentation of health care proxy forms increased (62–70%) as did Medical Order for Life Sustaining Treatment (1–11%) during the 6 months after the emergency department visit. Conclusion: A novel, emergency department-based, nurse-led brief motivational interview to stimulate serious illness conversations is feasible and may improve advance care planning engagement and documentation in seriously ill older adults.